2019
DOI: 10.1096/fj.201900326r
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol ameliorates ischemia/reperfusion‐induced tight junction disruption in brain endothelial cells by inhibiting endoplasmic reticulum stress

Abstract: Endoplasmic reticulum (ER) stress is essential for brain ischemia/reperfusion (I/R) injury. However, whether it contributes to I/R‐induced blood‐brain barrier (BBB) injury remains unclear, cilostazol exerts protective effects toward I/R‐induced BBB injury, with unclear mechanisms. This study explored the potential role of ER stress in I/R‐induced endothelial cell damage and determined whether the therapeutic potential of cilostazol, with respect to I/R‐induced endothelial cell damage, is related to inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…In this study, the upregulation of the three major ER transducers and their active forms indicated the activation of ERS in COL4A5 mutant fibroblasts. A similar phenomenon has been reported (Wang et al, 2017;Nan et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…In this study, the upregulation of the three major ER transducers and their active forms indicated the activation of ERS in COL4A5 mutant fibroblasts. A similar phenomenon has been reported (Wang et al, 2017;Nan et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…For example, ER stress was verified to be involved in Reticulon Protein 1-C-mediated cerebral I/R injury in MCAO rats (Gong et al 2017 ). Nan et al demonstrated that inhibiting ER stress was the mechanism of cilostazol relieving cerebral I/R injury-induced endothelial cell damage (Nan et al 2019 ). Therefore, ER stress inhibition can be an effective therapeutic strategy for cerebral I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the severe and continued ER stress may result in increased transcription of CHOP, an essential molecule in the apoptotic signaling pathway, and then trigger apoptosis (Tsai et al 2018 ). Previous studies suggested that attenuating ER stress could effectively relieve cerebral I/R injury (Feng et al 2019 ; Nan et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, ER stress was veri ed to be involved in Reticulon Protein 1-C-mediated cerebral I/R injury in MCAO rats (Gong et al 2017). Nan et al demonstrated that inhibiting ER stress was the mechanism of cilostazol relieving cerebral I/R injury-induced endothelial cell damage (Nan et al 2019). Therefore, ER stress inhibition can be an effective therapeutic strategy for cerebral I/R injury.…”
Section: Discussionmentioning
confidence: 99%